The first isolation of Campylobacter lanienae from chickens - Acik, M.N.; Karahan, M.; Ongor, H.; Karagulle, B.; Cetinkaya, B. (My University, 2013)
The aim of the present study was to determine the prevalence of Campylobacter jejuni, C. coli, C. lari and C. lanienae which are the most common causes of acute bacterial gastroenteritis in humans, in clinically healthy cattle, sheep and chickens. A total number of 2700 abattoir samples containing 150 intestinal contents and 150 gall bladders from each of the animal species in each of the three provinces located in the east of Turkey. Following the inoculation of the samples onto modified Charcoal Cefoperazone Deoxycholate Agar (mCCDA), Campylobacter spp. was isolated from 24.7% (667/2700). In the analysis of the isolates with species-specific Polymerase Chain Reaction (PCR), the identification percentages of Campylobacter species were determined as 78.1% for C. jejuni, 23.7% for C. coli, 1.2% for C. lanienae and 1.0% for C. lari. To the authors' knowledge, this study reports the isolation of C. lanienae in animals for the first time in Turkey and in chickens species for the first time in the world.
Keywords: C. coli; C. jejuni; C. lari; Campylobacter lanienae; Cattle; Chicken; Sheep